Processos de subjetivação do professor de surdos no ensino médio: narrativas de si - Barbosa, Romilda Meira De Souza (2021)
By force of Law, the deaf education teacher in high school has his discursive practices crossed by legal provisions of inclusion and Information and Communication Technologies (ICTs) and, in this web of discourses, they constitute a subject crossed by multiple (O)thers that, by/for/about him, speak in the absence of what he thinks and says. It is important to listen to him in order to know how his subjectivation is processed, how his representations are made through the bias of his discourses, which cross and constitute him, in order to problematize education based on what he says. In this way, we start from the assumption that the teacher, when narrating about what, how and for whom he teaches, tries to register in official speeches, which are intended to be regularized; we hypothesize that there is an attempt to identify the teacher subject with such discourses, under the knowledge-power strategy, since he is not subjective as a the deaf education teacher . Therefore, guided by the questioning of how the subjectification of deaf education teachers in high school we raise the following research questions: i. How is (dis)order constituted in the sayings of deaf education teachers in high school in relation to the official discourses of inclusion?; ii. What regularities of utterances materialize in the discourse of this subject teacher, about himself and the (O)ther?; iii. In the narratives of the self, how does the subjectivity of the subject teacher of the deaf occur in high school, from the perspective of discourses on the use of ICTs? Our general objective is to problematize the teacher's narratives, understanding them as written by themselves, in and through which their voice can be overheard about what it means to be a deaf education teacher in high school. Specifically, we aim to: 1) discuss possible meaning effects that permeate the teacher's narratives, under the bias of the functioning of the of in-exclusion process in the school; 2) interpret the representations that teachers have of themselves and of the (O)ther; and 3) to analyze, in the subjectivation process, how the (dis)identifications of the subject teacher occur with the official discourses that are conveyed and validated at school about students with deafness. When completing the theoretical-methodological plot, we based on transdisciplinarity: in the interface with Lacanian Psychoanalysis (LACAN, 1998, 2003, 2005) to understand the constitution of the subject in/by language, split and cleaved; in the discursive-deconstructive perspective, (DERRIDA, 2001a, 2003; CORACINI, 2007, 2015), for a problematizing reading of the discourse through which we can interpret the word in its ambivalence of meanings and deconstruct totalities; and in archaeology (FOUCAULT, 1979, 2007, 2014) as a device for the analysis of knowledge-power relations, in the understanding of the construction of (ab)normality and discursive practices, which are formulated from and in the form of circulating statements in the daily life of the school space. The corpus consists of selected excerpts from oral interviews (recorded and transcribed) of ten deaf education teachers in high school, in five state schools in Mato Grosso do Sul. The research is structured in two parts: the first one lists research carried out from teachers' narratives, as well as the locus of enunciation of the subjects to compose the conditions for the production of speeches, an aspect that encompasses and guides the reliability of the interpretation gesture; the second one brings the theoretical-methodological framework articulated to the analytical device to guide the reading gestures of the research axes, which are imbricated, constitutive of each other and allow us to glimpse, how the subject's sub(ob)jectivation of the subject teacher is processed in the narratives of themselves. In the (in)conclusive gestures of readings, always open to others, we interpret that the teacher, when speaking of the other, that is, of his practice, narrates himself, in the alterity and contradiction of being he (listener), the in-excluded , the “stranger” in his own home (the classroom), given the hos(ti)pitality relations with the many (O)thers who instigate him to (de)sharpen himself in the midst of the discourses that constitute him. In saying about him, the meanings of what it means, for him, to be subject / object of knowledge escape, in the web of discourses about / for him, to which he tries to identify himself as a form of resistance.